The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15184/aqy.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

Roman bazaar or market economy? Explaining tableware distributions through computational modelling

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The study of clay lamps is related to the researches in broad framework of Roman pottery, Craft and Commerce in the Roman Empire. In this sense, aligned with the most recent research in archaeological ceramics (Brughmans and Poblome 2016, Bes 2015, Carrignon 2015. The question of how frequent and intense the economic contacts would be in past, in addition to the specific case studied, is a topic of growing interest, fostering data sets that include archaeological, epigraphic, and written sources.…”
Section: Network Analysis and Archeologymentioning
confidence: 81%
“…The study of clay lamps is related to the researches in broad framework of Roman pottery, Craft and Commerce in the Roman Empire. In this sense, aligned with the most recent research in archaeological ceramics (Brughmans and Poblome 2016, Bes 2015, Carrignon 2015. The question of how frequent and intense the economic contacts would be in past, in addition to the specific case studied, is a topic of growing interest, fostering data sets that include archaeological, epigraphic, and written sources.…”
Section: Network Analysis and Archeologymentioning
confidence: 81%
“…This view is understandable given the fragmentary and time-averaged nature of the archaeological record. Instead, the approach used here treats social networks as dynamical systems with continuous flows of matter, information, and energy in constant interaction with their ecological and social environments (Brughmans and Poblome 2016;Crabtree 2015). Improved representations of social and biophysical dynamics will not only enhance understanding of the empirical settlement patterning in the archaeological record, but will also facilitate future cross-cultural and interregional comparisons by providing a shared set of questions and methodological tools for answering them.…”
Section: Discussionmentioning
confidence: 99%
“…Robust patterns in the geographical spread of such archaeological data can be explored as emerging from theorised Roman economic systems with varying degrees of integration (e.g. Graham and Weingart 2015;Brughmans and Poblome 2016a;2016b).…”
Section: Key Complexity Science Conceptsmentioning
confidence: 99%
“…Roman example: In the MERCURY model, Brughmans and Poblome (2016a;2016b) constructed an ABM consisting of traders trading goods within and across markets. By changing the properties of the commercial network (from well-connected within markets to well-connected between markets) they showed that only in scenarios where the market was well integrated (i.e., traders had access to contacts from outside their immediate surroundings) the resulting pattern of distribution of goods matched the archaeologically attested spatio-temporal trends in the distribution of Terra Sigillata in the Roman East.…”
Section: Agent-based Modelling Lead Author: Iza Romanowskamentioning
confidence: 99%
See 1 more Smart Citation